2015
DOI: 10.1177/1090198115580975
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening Among Dominican Latinas

Abstract: With the marked increase of the Latino population in the United States during the past 20 years, there has been growing interest in the social, cultural, and structural factors that may impede breast cancer screening among Latino women, especially among those subgroups that have been understudied. Acculturation and fatalism are central cultural constructs in these growing fields of research. However, there is great debate on the extent to which acculturation and fatalism affect breast cancer screening among La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 55 publications
0
12
0
1
Order By: Relevance
“…For instance, one cross-sectional study found that Korean-American women ≥ 65 years perceive breast cancer to be more serious compared to Korean-American women ≤ 65 years [48•] and a cross-sectional study of women ≥ 65 years from racially and ethnically diverse backgrounds found that women who are more worried about breast cancer were more likely to undergo screening [45]. In contrast, older Hopi women who feared a breast cancer diagnosis were less likely to undergo mammography screening [42] while a study among Dominican Latinas found no association between mammography behavior and the belief that there is not much one can do to keep from getting cancer or that cancer was a death sentence [40].…”
Section: Perceived Susceptibility and Perceived Seriousness Of Breastmentioning
confidence: 97%
“…For instance, one cross-sectional study found that Korean-American women ≥ 65 years perceive breast cancer to be more serious compared to Korean-American women ≤ 65 years [48•] and a cross-sectional study of women ≥ 65 years from racially and ethnically diverse backgrounds found that women who are more worried about breast cancer were more likely to undergo screening [45]. In contrast, older Hopi women who feared a breast cancer diagnosis were less likely to undergo mammography screening [42] while a study among Dominican Latinas found no association between mammography behavior and the belief that there is not much one can do to keep from getting cancer or that cancer was a death sentence [40].…”
Section: Perceived Susceptibility and Perceived Seriousness Of Breastmentioning
confidence: 97%
“…The authors point out that women living in rural areas of the United States receive mammography screening only when they have health insurance. Abraído-Lanza et al [ 20 ] studied Latino women living in the United States and found that cultural and logistical barriers lower breast cancer screening participation rates and suggested intensifying public health campaigns targeted at this public.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on social and cultural determinants of health care use among Latina immigrants in the US have primarily focused on older, US-born Latinas or Latina immigrants residing in the US for many years (Abraído-Lanza, Martins, Shelton, & Flórez, 2015; Asamoa et al, 2004; Fuentes-Afflick & Hessol, 2009; Garcés, Scarinci, & Harrison, 2006). Understanding potential determinants of health care soon after immigration to the US among young women may foster an evidence base for early interventions targeting health disparities affecting Latina young adults as well as similar immigrant populations internationally.…”
mentioning
confidence: 99%